Macro Growth from Micro Creativity: Optimizing the Entrepreneurial Empowerment Potential of Agate MSMES in Creative Industrial Economics - Sariat Arifia; Zaid; Sudjatmiko (International Journal of Small and Medium Enterprises and Business Sustainability, 2024)
Agate, as one of the many precious stones that are part of Indonesia's cultural heritage and natural resource wealth, offers significant potential to drive the creative economy through the creativity of its craftsmen. This potential is rooted in micro, small, and medium enterprises (MSMEs) and millions of people involved in all villages across Indonesia. However, in reality, the empowerment of MSMEs as creative industry players is not yet optimal. This research aims to examine how the potential for agate economic activities through MSME entrepreneurship can be optimized into a creative industry that contributes to Indonesia's macro economy. Additionally, it investigates the legal protection for agate MSME actors in Indonesia so far. The research method used is qualitative, exploring a deeper understanding of the phenomenon by considering personal experiences, direct observations, and analyzing relevant texts and literature. Thus, the data sources in this research include not only secondary data, such as scientific journal articles and book chapters but also field observations that have not previously been documented textually. The theories discussed encompass entrepreneurship, MSME empowerment, and product legal protection to enable Indonesia to achieve optimal macroeconomic growth based on microeconomics. The research results show that the potential for agate economic activities through MSME entrepreneurship still needs to be optimized. This can be achieved through the integration of regulation, working programs, and the involvement of all stakeholders, transforming MSMEs into a cohesive, modern, and integrated creative industry that significantly contributes to Indonesia's macro economy. Optimization is crucial to capture market opportunities both domestically and internationally, converting partially traditional MSMEs into a large-scale creative industry.